2017
DOI: 10.1016/j.jpha.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Anti-atherosclerotic activity of root bark of Premna integrifolia Linn. in high fat diet induced atherosclerosis model rats

Abstract: Premna integrifolia Linn. is a medicinal plant used in “Dhasamula” drug preparation of Ayurvedic systems of medicine in the treatment of various ailments like bronchitis, dyspepsia, liver disorders, piles, constipation, hyperlipidemia and fever. The anti-atherosclerotic activity of hydroalcoholic extract (HAE) of root bark of P. integrifolia was evaluated in high fat diet induced atherosclerosis rats. Sixty Wistar rats were divided into six groups: the first group served as control, the second group was fed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…Bais et al [34] showed a decrease in HDL-c in rats subjected to hyperlipidic diet for 49 days. However, neither colocynth alkaloids nor glycosides significantly changed plasma HDL-c levels, similarly to the reports by Ibekwe et al [35] and Subramani et al [36]. The observed highly significant increase in LDL-cholesterol plasma levels in rats on HFD is in agreement with other studies [36].…”
Section: Plasma Biochemical Parameters In Control and Hfd Rats And Insupporting
confidence: 92%
See 1 more Smart Citation
“…Bais et al [34] showed a decrease in HDL-c in rats subjected to hyperlipidic diet for 49 days. However, neither colocynth alkaloids nor glycosides significantly changed plasma HDL-c levels, similarly to the reports by Ibekwe et al [35] and Subramani et al [36]. The observed highly significant increase in LDL-cholesterol plasma levels in rats on HFD is in agreement with other studies [36].…”
Section: Plasma Biochemical Parameters In Control and Hfd Rats And Insupporting
confidence: 92%
“…However, neither colocynth alkaloids nor glycosides significantly changed plasma HDL-c levels, similarly to the reports by Ibekwe et al [35] and Subramani et al [36]. The observed highly significant increase in LDL-cholesterol plasma levels in rats on HFD is in agreement with other studies [36]. Treatment with the colocynth glycosides decreased plasma LDL-cholesterol levels.…”
Section: Plasma Biochemical Parameters In Control and Hfd Rats And Insupporting
confidence: 91%
“…After 30 days many viable results were collected in which there were highly reductions in atherosclerosis, lipid deposition, HMG-Co reductase and other some other factors that are highly induced for the development of atherosclerosis. This plant is proved as potential for anti -atherosclerotic activities (Subramani et al, 2017).…”
Section: Premna Integrifoliamentioning
confidence: 99%
“…An elevated atherogenic index is considered one of the significant markers of atherosclerosis [ 11 ]. In our study, the atherogenic condition promisingly improved in animals that encountered a dose of 400 mg/kg b.w./day, p.o.…”
Section: Discussionmentioning
confidence: 99%